Analisis Rencana Layanan Lumpur Tinja Terjadwal (L2T2) untuk Manajemen Layanan Lumpur Tinja yang Berkelanjutan di Kota Cilacap - Agus Sudrajat; Sudarno Sudarno; Yanuar Luqman (Seminar Nasional Lahan Suboptimal, 2020)
Sudrajat A, Sudarno S, Luqman Y. 2020. Analysis of scheduled faecal sludge service (SFSS) for sustainable faecal sludge management in Cilacap. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).In accordance with the 6’th Sustainable Development Goals (SDG's), that ensurin availability and sustainable management of water and sanitation for all and with the launch of the 100-0-100 movement by Indonesian Government, which is a program to achieve the 100% access for water, 0%  for slums, and 100% access to proper sanitation, Cilacap government need to work harder to achieve 100% access to proper sanitation especially in faecal sludge management that still needs to be improved. More than 98% households in Cilacap are using on-site sanitation system, without periodicaly emptied, and its causing problems in public health, and has impact for environmental and economic nearby communities. This study was held in Cilacap, a municipal in Central Java, Indonesia, using secondary data and literature review. This study aims to analyze feseability of the plan of implementation Scheduled Faecal Sludge Service (SFSS). Based on analysis, Cilacap are feasible to implementing SFSS as long as Cilacap could ensure to repair all gaps that shown in Gap analysis. Data of sludge service areas in cilacap, operating patterns, SFSS implementation procedures, and financial calculations must be made on preparation stage of SFSS.